EVALUASI DAN STRATEGI PERBAIKAN PRODUKSI BERKELANJUTAN USAHA PENYEMBELIHAN AYAM SKALA KECIL - Luki Hidayati; Sucipto Sucipto; Retno Astuti; Herawati Herawati (AGROINTEK, 2021)
Recently, industry and consumers demand that sustainable production were necessary, one of them is chicken slaughtering. The methods to evaluating the sustainable production for small-scale chicken slaughtering has not been well established. The purpose of this study is index performance evaluation and improvement strategies formulation of sustainable production in small- scale chicken slaughtering. Key Performace Indicators (KPI) were used as the measuring instruments. Composite Index (CI) was used to compute the KPIs into Sustainable Production Performance Index (SPPI). The SPPI was compute on 16 KPIs. The CI stages is actual value of KPI measurement, normalization the KPI, weighting the KPI using Fuzzy-Analytical Hierarchy Process (F-AHP), and linear aggregation. The results showed that the Overall SPPI values at two small-scale chicken slaughtering obtained is 51.30 % and 63.99 %. Both of the Overall SPPI is classified as 'fair' by the rating standard. Generally, the improvement strategies are reduce the manufacturing costs by managing the labor costs effiently and reducing overhead costs. Increase the productivity by managing the production capacity and yield. Waste minimization by recycling the solid waste such as feathers. Improve the halal production practices by following the halal slaughtering aspects, forming internal halal management teams, and participating in halal training. The improvement strategies is expected to increase the sustainable production performance indexes in small-scale chicken slaughtering.Keywords: Composite Index; Chicken Slaughtering; Improvement Strategeies; Key Performance Indicators (KPI)